Hearing-related problems in children with cleft palate: A single-center cross-sectional study in the sub-Himalayan population - Vishal Mago; Arush Pasricha; Hiteswar Sarma; Praveen A Jayaprakash; Madhubari Vathulya; Debarati Chattopadhyay (Wolters Kluwer Medknow Publications, 2023)
Purpose: Cleft palate is known to cause recurrent otitis media with hearing loss. Various studies have stated the incidence of middle ear disease in patients with cleft palate is around 90%. The anomalous position of the Eustachian tubes in patients with cleft palate leads to otitis media with effusion. If left uncorrected this leads to complications such as cholesteatoma, retraction pockets, and atelectasis leading to permanent hearing loss. In this study, we evaluated the children presenting to our institute with cleft palate for hearing-related issues. Materials and Methods: The study was conducted in our institute from January 2017 to September 2020. It was a cross-sectional study, where 45 children with cleft palate were compared with 36 children with cleft lip who were considered the control group. Hearing of all children was assessed using tympanometry, otoscopy, and brainstem evoked response audiometry (BERA). Results: About 93.3% of children in the cleft palate group had an abnormal tympanic membrane on otoscopy, whereas in the control group only 11.1% of children had an abnormal tympanic membrane on otoscopy. About 97.8% of children in the cleft palate group had a hearing threshold greater than 25 decibels, whereas only 13.9% of children in the control group had a hearing threshold of above 25 decibels. More children in the cleft palate group had an abnormal tympanogram (42.2% had a type B tympanogram and 46.7% had a type C tympanogram) compared to the control group (5.6% had a type B tympanogram and 2.8% had a type C tympanogram). Conclusion: Our study adds to the evidence that there is a high incidence of hearing impairment in children with cleft palate. Hence, we advocate that early identification by screening measures such as otoscopy, tympanometry, auditory brainstem response, and pure tone audiometry during the first visit itself in these children so that early treatment can be initiated.